Conceptual Framework for Fintech in Sharia Financial Planning - Masmuh, Muhammad Mukti Arif; Rahmawati; Fahmi, Muhammad (Li Falah: Journal of Islamic Economics and Business, 2024)
This study aims to develop a framework that can increase the use of financial technology (fintech) in Islamic financial planning, which is expected to support sustainable economic development for individuals and institutions. The method used is a descriptive literature study, which collects data from various sources such as scientific journals, books, and related reports. The results of the study show that the application of fintech in Islamic financial planning can provide easy access and increase financial inclusion in Muslim communities, especially in Indonesia. This study also identified five important processes in the development of fintech for Islamic financial planning: identification, customers, standardisation, technology, and realisation. The implications of this study are the importance of cooperation between Islamic financial institutions and fintech companies to create innovative solutions that are in accordance with Sharia principles, as well as the need to develop policies that support the Sharia fintech ecosystem in Indonesia.